1981
DOI: 10.1063/1.442168
|View full text |Cite
|
Sign up to set email alerts
|

The isotope exchange reactions H++D2⇄HD+D+ and D++H2⇄HD+H+ in the temperature range 200–300 K

Abstract: Nearresonant vibrational energy transfer in ozone. Doubleresonance measurements and calculations in the temperature range 200-300 K Forward and reverse rate coefficients have been measured in the temperature range 200-300 K for the two reactions H+ + D,-=HD + D+ and D+ + H,-=HD + H+. Equilibrium constants derived therefrom agree with theoretical van't Hoff plots calculated from statistical mechanics and confirm the temperature calibration of the SIFT apparatus used. It is suggested that these reactions can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
39
0
2

Year Published

1984
1984
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 15 publications
10
39
0
2
Order By: Relevance
“…19 up to E c ∼ 0.18 eV, and within the experimental uncertainties of some other ion beam techniques for larger energies up to ∼1 eV. 47 The comparison of thermal rate constants between 100 and 500 K revealed that the statistical predictions are larger than both QM and QCT results, but are on the contrary, perhaps accidentally, the closest theoretical rates to the measurements by Henchman et al 18 Recently, some of us have carried out TIQM calculations on the D + +H 2 → HD+H + reaction to obtain ICSs and thermal rate constants at low temperature. 49 The comparison with previous experimental work 19,50 revealed that the calculation reproduced rate constants beyond a collision energy of 0.006 eV.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…19 up to E c ∼ 0.18 eV, and within the experimental uncertainties of some other ion beam techniques for larger energies up to ∼1 eV. 47 The comparison of thermal rate constants between 100 and 500 K revealed that the statistical predictions are larger than both QM and QCT results, but are on the contrary, perhaps accidentally, the closest theoretical rates to the measurements by Henchman et al 18 Recently, some of us have carried out TIQM calculations on the D + +H 2 → HD+H + reaction to obtain ICSs and thermal rate constants at low temperature. 49 The comparison with previous experimental work 19,50 revealed that the calculation reproduced rate constants beyond a collision energy of 0.006 eV.…”
Section: Introductionsupporting
confidence: 65%
“…Some of the earliest experimental work on the exchange D + +H 2 →H + +HD reaction has been devoted to measure rate constants. [15][16][17][18][19] Holliday et al 20 reported integral cross sections (ICSs) and energy distributions obtained in a tandem mass spectrometer experiment. A great deal of the theoretical investigation on the title reaction has considered a large enough energy domain to cover the electronic crossing between the energy curves of the states correlating to H + +HD and HD + +H at about 1.6 eV above the H 2 well minimum.…”
Section: Introductionmentioning
confidence: 99%
“…The values (GIB 92) have a weak maximum at 300 meV and fall slowly below 1:5 × 10 −9 cm 3 s −1 at the lowest nominal collision energy achieved, 25 meV. The two VT-SIFT results measured by Henchman et al (1981) are shown as solid triangles. They appear to indicate another temperature trend.…”
Section: + + Hmentioning
confidence: 99%
“…This simplest of the chemical reactions has been studied extensively both experimentally and theoretically. As a result the dynamics of H-D exchange processes at low energies is well understood, also for other isotopic modiÿcations (Henchman et al, 1981;Gerlich, 1982). A selection of experimental results obtained until 1990 have been summarized in a review by Gerlich (1992), see for example 75,76,85 and 87 therein.…”
Section: + + Hmentioning
confidence: 99%
See 1 more Smart Citation